Resveratrol como meio de estocagem para dentes avulsionados: estudo in vitro da viabilidade celular - Hamanaka, Elizane Ferreira [UNESP] (2014)
The maintenance of avulsed teeth in appropriate storage media for the preservation of cell viability is very important for the repair of the periodontal ligament and to prevent the development of root resorption, which is the main cause of loss of replanted teeth. Recently, resveratrol has been extensively studied due to its antioxidant, anti-inflammatory and antimicrobial properties and ability to prolong the lives of several organisms since yeast to mammals. Thus, the aim of this study is to evaluate the effectiveness of resveratrol as storage media for avulsed teeth by measuring the structural and functional cell viability. The resveratrol dissolved in propylene glycol + phosphate-buffered saline (PBS), which was control of the solution, was tested. UHT milk was used as a comparative storage medium because it is traditionally used and indicated to this purpose. The positive controls used were Dulbecco's Modified Eagle's Medium (DMEM) and PBS, and the water as negative control. Two cell types were used: human peripheral blood mononuclear cells and human periodontal ligament fibroblasts maintained in culture and the cell viability was analyzed by Trypan Blue exclusion test and the tetrazolium salt-based colorimetric assay (MTT) and determined at 1, 3, 6, 10 and 24 h of incubation. The tests were performed in triplicate and with 4 replications. The resveratrol presented good results with both cell types when analysed by Trypan Blue exclusion test. There were no differences between milk and resveratrol over time. When analysed by MTT assay, resveratrol presented inferior results than milk and positive control DMEM (p<0,05). Based on these results, it may be concluded that resveratrol was able to maintain the structural cell viability of the human peripheral blood mononuclear cells and periodontal ligament fibroblasts by Trypan...